Toxoplasma gondii infection in children after allogeneic hematopoietic stem cell transplantation: A case report and literature review - Lijuan Luo; Nan Shen; Wenjuan Chen; Chengjuan Luo; Xiaohang Huang; Yuelian Jiang; Qing Cao (Wiley, 2021)
ABSTRACT Introduction Toxoplasmosis is a life‐threatening complication after hematopoietic stem cell transplantation (HSCT). However, for several reasons, clinicians know little about Toxoplasma infection. Case presentation We report a case of toxoplasmosis that was diagnosed by bone marrow smear and metagenomic next‐generation sequencing (mNGS) after HSCT in a boy. Additionally, we summarize the characteristics of toxoplasmosis after pediatric HSCT reported in the literature published in PubMed. Conclusion Clinicians should increase their awareness of toxoplasmosis in children after HSCT and implement pre‐transplant screening and post‐transplant monitoring and prevention in future according to the national conditions of our country.